I just lately started buying wings : missives from the other side of silence - Kupperman, Kim Dana. (Minneapolis, Minn. : Graywolf Press, 2010)
From the depths of a chaotic family romance to the winds spreading Chernobyl's nuclear fallout, Kupperman's episodic missives add up to a life-- her life.
'Kupperman is the recipient of the 2009 Katherine Bakeless Nason Prize in Nonfiction ... awarded by the Middlebury College Bread Loaf Writers' Conference.'--P. [201].
Keywords: Kupperman, Kim Dana; American essays -- 21st century; Women authors -- 21st century -- Biography